Test methods for electrical materials, printed boards and other interconnection structures and assemblies. General test methods for materials and assemblies. An intercomparison evaluation to implement the use of fine-pitch test structures for surface insulation resistance (SIR) testing of solder fluxes in accordance with IEC 61189-5-501 Part 5-506, (18th July 2019) - British Standards Institution,
No abstract available